The Analgesic Effect of Cryotherapy on Patients Undergoing Extracorporeal Shock Wave Lithotripsy: A Randomized Controlled Trial - Pimratana, Chaowat; Hengsawat, Kornkanok (Siriraj Medical Journal, 2022)
Objective: To compare the degree of pain between cryotherapy and standard preoperative care in the treatment of urolithiasis with extracorporeal shock wave lithotripsy (ESWL). Materials and Methods: A total of 180 ESWL patients were randomly assigned to experience the standard preoperative method, or additional cryotherapy (ice pack application on the ESWL site) for 10 minutes before ESWL. The primary outcome was the maximum difference of pain intensity score from baseline during ESWL and the secondary outcomes, which were analgesic consumption, pulse rate, adverse events, stone free rate, and complications that were gathered and analyzed. Results: The maximum change in pain intensity score from baseline during ESWL in the cryotherapy group was significantly lower than in the control group (VAS score 4.0±1.9 vs. 5.2±2.7, p=0.002). The cryotherapy group showed significantly less total fentanyl consumption than the control group (85.3±22.0 mcg vs. 93.6±25.6, p=0.021). We found no significant difference in stone free rate, adverse events or complications in either group. Conclusion: Preoperative cryotherapy using ice packs for 10 minutes can provide an effective analgesic for ESWL. Adequate pain control with cryotherapy should be an option of pain management during ESWL.